Lorna Doone - Penn, David; Gibson, Dylan; Blackmore, R. D. (Richard Doddridge), 1825-1900. (Oxford : Oxford University Press, 2008)
One winter's day in 1673 young John Ridd is riding home from school, across the wild lonely hills of Exmoor. He has to pass Doone valley - a dangerous place, as the Doones are famous robbers and murderers. All Exmoor lives in fear of the Doones...
2
Keywords: Readers